Pengaruh Pemahaman Peraturan Perpajakan, Tarif Pajak, Asas Keadilan, dan Tingkat Pendidikan terhadap Kepatuhan Wajib Pajak UMKM di Kabupaten Kudus - Helmalia Puteri; Nafi’ Inayati Zahro; Febra Robiyanto (Bulletin of Community Engagement, 2024)
Tax is one of the crucial sources of state revenue to fund various development programs and provide public services. In Indonesia, a lack of understanding of tax regulations often leads to low levels of taxpayer compliance, especially in the Micro, Small, and Medium Enterprises (MSMEs) sector. In Kudus Regency, the low number of SPT reports indicates a compliance problem among MSME taxpayers. This problem is further exacerbated by external factors such as the COVID-19 pandemic, which has caused many MSMEs to experience a decline in turnover and financial difficulties. Many MSME actors feel that the obligation to pay taxes reduces their income, so they often ignore their tax obligations. This study aims to analyze the effect of understanding tax regulations, tax rates, the application of the principle of justice, and education levels on taxpayer compliance. The focus of the study was directed at MSME taxpayers registered at the Kudus Pratama Tax Service Office (KPP), with the aim of obtaining a comprehensive picture of the factors that influence tax compliance among MSMEs. The purposive sampling method was used in data collection, with a sample consisting of 400 respondents. Data analysis was conducted using multiple linear regression techniques processed with SPSS statistical software version 26. The results of the study showed that each independent variable, namely understanding of tax regulations, tax rates, application of the principle of justice, and level of education, partially had a significant and positive effect on increasing taxpayer compliance.